Prioritization Regression Testing Techniques: a Review - Sondhi, Nitin; Singh, Vimal (International Journal of Engineering and Technology, 2018)
Regression Testing is very important method that is being performed once the software is live and afterward comes for some changes. It is a testing techniques that ensures that the previously developed software still works as expected after performing changes in it. Whenever any change is being performed in the software, regression testing is being performed to make sure that previously working module works fine even after the change is being made. Complete Regression Testing is practically impossible. So one alternative is to minimize the regression test cases. In the paper various regression testing techniques has been compared and then the conclusion has been drawn about which one is better based on the problem at hand.Â Â